The vibrational relaxation of CO₂ isolated in solid argon - Cenian, A.; Grigorian, G.; Śliwiński, G. (Физика низких температур, 2003)
For description of the vibrational relaxation of CO₂ molecules embedded in Ar matrix the model based on multiphonon transitions is applied. Rates for the VT and VV processes are determined from a fitting of simulated and experimental data. The calculations confirmed that radiative processes influence significantly the vibrational energy relaxation of CO₂ embedded in solid Ar, e.g., the determined rate for energy transfer between n₃ and n₂. mode is significantly lower than that predicted under assumption of the nonradiative relaxation.